(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
This paper examines some of the basic differences and contradictions between Husserlian phenomenology and existential thinking, thereby questioning the possibility or impossibility of elaborating a genuinely ‘existential phenomenology’. I will argue that an answer to this question may be found within the post-Cartesian philosophy of Maurice Merleau- Ponty.